Tau promotes oxidative stress-associated cycling neurons in S phase as a pro-survival mechanism: Possible implication for Alzheimer's disease. (April 2023) - Denechaud, Marine; Geurs, Sarah; Comptdaer, Thomas; Bégard, Séverine; Garcia-Núñez, Alejandro; Pechereau, Louis-Adrien; Bouillet, Thomas; Vermeiren, Yannick; De Deyn, Peter P.; Perbet, Romain; Deramecourt, Vincent; Maurage, Claude-Alain; et al.
Abstract: Multiple lines of evidence have linked oxidative stress, tau pathology and neuronal cell cycle re-activation to Alzheimer's disease (AD). While a prevailing idea is that oxidative stress-induced neuronal cell cycle reactivation acts as an upstream trigger for pathological tau phosphorylation, others have identified tau as an inducer of cell cycle abnormalities in both mitotic and postmitotic conditions. In addition, nuclear hypophosphorylated tau has been identified as a key player in the DNA damage response to oxidative stress. Whether and to what extent these observations are causally linked remains unclear. Using immunofluorescence, fluorescence-activated nucleus sorting and single-nucleus sequencing, we report an oxidative stress-associated accumulation of nuclear hypophosphorylated tau in a subpopulation of cycling neurons confined in S phase in AD brains, near amyloid plaques. Tau downregulation in murine neurons revealed an essential role for tau to promote cell cycle progression to S phase and prevent apoptosis in response to oxidative stress. Our results suggest that tau holds oxidative stress-associated cycling neurons in S phase to escape cell death. Together, this study proposes a tau-dependent protective effect of neuronal cell cycle reactivation in AD brains and challenges the current view that the neuronal cell cycle is an early mediator of tau pathology. Graphical abstract: ga1 Highlights: In AD brains, cycling neurons near amyloid plaques accumulate nuclear tau. Nuclear tau + cycling neurons in AD brains are confined in S phase. Oxidative stress triggers neuronal cell cycle re-entry and increased nuclear tau. Tau downregulation blocks the neuronal cell cycle progression to S phase. Tau downregulation activates neuronal apoptosis.